Thermal performance evaluation of heat exchanger tubes equipped with coupling twisted tapes - Eiamsa-Ard, S.; Nanan, K.; Thianpong, C.; Eiamsa-Ard, P. (My University, 2013)
The present work has been conducted to investigate the effect of coupling twisted tapes on heat transfer enhancement in a heat exchanger. The effects of (1) twisted tape orientation (co-coupling twisted tapes or counter-coupling twisted tapes), (2) width ratio, and (3) twist ratio were also examined. Results of coupling twisted tapes were also compared to those of a typical twisted tape. Experimental results showed that the use of counter-coupling twisted tapes resulted in higher heat transfer, friction loss, and thermal performance factor than that of co-coupling twisted tapes and typical twisted tapes. Thermal performance factor increased as twist ratio and Reynolds number decreased while width ratio increased. © 2013 Taylor & Francis Group, LLC.
Keywords: coupling twisted tapes; heat exchanger; heat transfer enhancement; swirl flow; turbulence